Political economy of labor repression in the United States - Kolin, Andrew 1955- (Lexington Books, 2017)
"The role of the state is not [to] be overlooked in its support of elite control over production, as well as aiding through legal means the growth of a capitalist economy in opposition to labor's conception of greater economic democracy. This book explains how and why labor continues to confront repression in the twentieth and twenty-first centuries." --Back cover.